The Constitutional Dimensions of Church Property Disputes - Louis J. Sirico Jr. (Washington University Law Quarterly, 1981)
This Article explains how the Supreme Court has dealt with the underlying problems of church-state relationships.
Keywords: Watson v. Jones 80 U.S. (13 Wall.) 679 (1872); Church and state; Church property; Freedom of religion; United States